1994
DOI: 10.1016/0378-1097(94)90452-9
|View full text |Cite
|
Sign up to set email alerts
|

The α subunit of RNA polymerase specifically inhibits expression of the porin genes ompF and ompC in vivo and in vitro in Escherichia coli

Abstract: Overproduction of the alpha subunit of RNA polymerase in Escherichia coli resulted in inhibition of transcription of two osmoregulated porin genes, ompF and ompC, but not of constitutively expressed housekeeping genes. Overproduction of the sigma subunit did not have any inhibitory effects. The specific inhibitory effect of the alpha subunit was also found to depend upon the OmpR protein, the transcriptional activator for ompF and ompC. These results are in general agreement with other biochemical and genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…This nature of rpoA mutation was suggested, though not demonstrated, in a previous study of OmpR-activated promoters in E. coli (36). Indeed, in a separate study, overexpression of a was shown to reduce OmpR-dependent activation of the ompF and ompC promoters (6 (32). Our observation that greater overproduction of at from pNMD120 caused reduction also of PRN and FIM expression is consistent with this model, though it does not provide compelling evidence for it.…”
Section: Discussionsupporting
confidence: 51%
“…This nature of rpoA mutation was suggested, though not demonstrated, in a previous study of OmpR-activated promoters in E. coli (36). Indeed, in a separate study, overexpression of a was shown to reduce OmpR-dependent activation of the ompF and ompC promoters (6 (32). Our observation that greater overproduction of at from pNMD120 caused reduction also of PRN and FIM expression is consistent with this model, though it does not provide compelling evidence for it.…”
Section: Discussionsupporting
confidence: 51%
“…In addition to DNA binding, OmpR was shown to interact productively with RNA polymerase to effectively regulate its transcription (Bowrin et al, 1994). Analysis of OmpR structure also revealed that the large loop connecting helices a2 and a3 in the N-terminal region was the probable site of interaction with the a subunit of RNA polymerase RpoA (Martinez-Hackert & Stock, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…4) (Bowrin et al 1994;reviewed in Pratt & Silhavy 1994). The ¹35 and ¹10 regions of the ompF and ompC genes have low identity (50%) with the consensus sequence which necessitates binding of OmpR-P, a j70 type DNA binding protein, for transcriptional regulation (Mizuno et al 1983a,b).…”
Section: Differential Regulation Of Ompf and Ompc By Ompr-pmentioning
confidence: 99%